1973
DOI: 10.1099/00207713-23-4-381
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of Bordetella and Related Organisms of the Families Achromobacteraceae, Brucellaceae, and Neisseriaceae

Abstract: A numerical taxonomic study was made of strains belonging to the genera Bordetella, Alcaligenes, Brucella, Acinetobacter, Moraxella, Neisseria, Haemophilus, Actinobacillus, and Pasteurella, together with a few strains from allied genera. They were examined for 139 characters covering a wide range of tests and properties. The strains fell into two major groups. Group A contained Haemophilus, Actinobacillus, and Pasteurella. Group B contained eight main clusters, representing, respectively, Bordetella pertussis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

1979
1979
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 42 publications
(17 reference statements)
2
28
0
Order By: Relevance
“…Based on a numerical analysis of 112 phenotypic characters, Johnson and Sneath (31) suggested that the family Brucellaceae should contain the following three genera: Brucella, Bordetella, and Alcaligenes. Our rRNA hybridization data (Table 1) show that this is impossible.…”
Section: Dna Base Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on a numerical analysis of 112 phenotypic characters, Johnson and Sneath (31) suggested that the family Brucellaceae should contain the following three genera: Brucella, Bordetella, and Alcaligenes. Our rRNA hybridization data (Table 1) show that this is impossible.…”
Section: Dna Base Compositionmentioning
confidence: 99%
“…], University Marburg, Federal Republic of Germany, 1979) or the Alcaligenaceae (16). On the basis of a numerical analysis of phenotypic features, Johnson and Sneath (31) proposed that the number of genera in the family Brucellaceae should be reduced to three, Brucella, Bordetella, and Alcaligenes. This proposal was not followed in Bergey's Manual of Determinative Bacteriology, 8th ed.…”
mentioning
confidence: 99%
“…Its fastidiousness and defined growth requirements (Proom, 1955) make it difficult to isolate without specialized media (Regan & Lowe, 1977) and identification is hampered by the close similarity of members of the genus Bordetella with other bacterial genera, in particular Haemopbilzrs, Acinetohacter and Alcaligenes (Johnson & Sneath, 1973). Considered an obligate respiratory tract pathogen for man (Linneman & Perry, 1977 ;Pittman, 1984) it has recently been isolated from the respiratory tract of healthy and pneumonic lambs in New Zealand (Cullinane e t al., 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators looked for genetic affinities by using transformations (5,12,29,31) or determined the fatty acid composition (26,37). Most studies, however, were of a phenotypic nature (3, 8, 24,28,36,[38][39][40][41]46). Our DNA:rRNA hybridization results were also used to assign strains to the genus Acinetobacter and to examine the relationship of some misnamed strains to this genus.…”
mentioning
confidence: 99%